Isolation of Microorganisms from Salt Lakes in the Dry Valley, Antarctica, and Their Living Environment - Osamu WAGURI (National Institute of Polar Research, 1976)
Isolation of microorganisms and determination of gases dissolved in waters of unfrozen salt lakes in the Dry Valley of Antarctica were carried out, as part of the Dry Valley Drilling Project (DVDP) of the Mc-Murdo Sound region during the 1974-1975 summer season. Samples were collected in and around the Lakes Bonney, Fryxell and Vanda. Gas-chromatographic and GC-Mass spectrometric analysis of these liquid gaseous samples revealed oxygen, nitrogen and carbon dioxide from in waters of all lakes, and methane and unknown gas (m/e 22) were detected in waters of Lakes Bonney west lobe and Vanda. Eumycetes were isolated from the samples collected one species from the bottom water of Lake Bonney east lobe, three species from surface water of Lake Fryxell and thirteen species from other samples than from salt lakes. Fourteen species of these isolates have not been reported before from Antarctica. Two or more species of bacteria were isolated from the bottom water of Lake Fryxell. One species was gram-positive rods and the other was gram-negative vibrio type bacterium with stalk. The stalked bacterium seems to be an unknown species of Caulobacter. Reports of the isolation of bacteria of this type in Antarctic samples have not been published to date.